Design And Implementation Of A Smart Meter - Kh.N. Polvonov; M.Z. Muqumov (Zeta Repository, 2023)
This paper presents smart system design and smart electricity meter design using global system Arduino microcontroller mobile communication (GSM) module and liquid crystal display (LCD).